KAJIAN PEMANFAATAN LIMBAH TEPUNG TAPIOKA SEBAGAI SUBMERGE CULTURE DALAM FERMENTASI ASAM SITRAT - Hamad, Alwani (UMP, 2010)
Tapioca starch waste usually had a problem after long time and then cause bad smelly and make pollution to the river. In this study, it can be use as sub-merge in citric acid fermentation used Aspergilus niger. the process was observed at pH variable from 2 - 5. Duration of the incubation time was also observed on day 5 to 9. Three important stages in the fermentation process was the preparation of media and media-making starter cultures. The citric acid produced from tapioca waste had yield 30.23% and the incubation time for 9 days with the acquisition reaches 43.51%. Then compared with the acquisition of citric acid from cassava was getting results that the acquisition of cassava citrate still had good result. It because the carbohydrate content of cassava was higher than on tapioca waste. Â Key word : Asam sitrat, limbah tapioka, fermentasi, sub-merge